"INVESTIGATION OF PREVALENCE OF BETA THLASSEMIA IN IRANIAN PROVINCES " - D.D. Farhud; H. Sadighi (Tehran University of Medical Sciences, 1997)
14,849 affected cases of beta thalassemia have been registered in 1995 in all provinces of Iran. It is estimated that there are about three million carriers in Iran. The provincial distributions of the affected cases show that the highest incidence in 100 thousand individuals was in Mazandaran (71.29) and Gilan (57.61), respectively, both near the Caspian sea (north), followed by Hormozgan (50.22), Khouzestan (48.79) , Kohkiluyeh & Boyr-Ahmad (48.42), Fars (47 20) (south) and the lowest in the north eastern province , Khorassan (1.23) followed by east and west Azerbaijan (2.21 , 2.91) in the north west of Iran.